2005
DOI: 10.1124/dmd.105.005264
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of human monocarboxylate transporter 6 (SLC16A5)

Abstract: ABSTRACT:Human monocarboxylate transporter 6 (MCT6) has recently been isolated, and its tissue distribution has been established at the mRNA level, but its functional properties remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 28 publications
5
84
0
Order By: Relevance
“…7 Far less is known about the remaining family members up to now, although the number of studies to characterize the remaining orphan MCTs is increasing. For instance, for MCT6 transport of xenobiotics, such as loop diuretics (e.g., bumetanide), the antidiabetic drug nateglinide or the uricosuric agent probenecid was described 8, 9. In addition, in contrast to the typical MCT substrates, dietary flavonoids were recently proposed as substrate for MCT6, with additional inhibiting effect,10 suggesting distinct substrate specificities compared with MCT1–MCT4.…”
Section: Substrates Of Mct Transportersmentioning
confidence: 99%
“…7 Far less is known about the remaining family members up to now, although the number of studies to characterize the remaining orphan MCTs is increasing. For instance, for MCT6 transport of xenobiotics, such as loop diuretics (e.g., bumetanide), the antidiabetic drug nateglinide or the uricosuric agent probenecid was described 8, 9. In addition, in contrast to the typical MCT substrates, dietary flavonoids were recently proposed as substrate for MCT6, with additional inhibiting effect,10 suggesting distinct substrate specificities compared with MCT1–MCT4.…”
Section: Substrates Of Mct Transportersmentioning
confidence: 99%
“…We have previously shown that MCT6 transports bumetanide, nateglinide, probenecid, and prostaglandin F 2a , but not L-lactic acid or L-tryptophan, which are typical substrates for MCT1-MCT4 and T-type amino acid transporter 1, respectively (Murakami et al, 2005). MCT6-mediated bumetanide uptake was pH-and membrane potential-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the recent characterization of MCT6 showed that this isoform was involved in the transport of diuretics, such as bumetanide, and did not transport monocarboxylates (3).…”
Section: Influence Of Mcts On the Disposition Of Other Drugsmentioning
confidence: 99%
“…MCTs (SLC16A) were first identified in the mid-nineties and to date 14 members of this family have been identified through sequence homology (1,2). Currently, seven isoforms have been functionally characterized and it has been demonstrated that not all members function as proton-coupled transporters and that a wide variety of endogenous and exogenous compounds are substrates, including lactate, pyruvate, butyrate, γ-hydroxybutyrate, bumetanide, and simvastatin acid (3)(4)(5)(6). In contrast, the SMCT family contains only two members, SLC5A8 and SLC5A12, which were identified within the past 5 years (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%